Peran dan Persepsi Ayah dalam Mendukung Pemberian ASI Ekslusif: Sebuah Perspektif Health Belief Model - Sabilla, Mizna; Bahri, Syaiful; Ariasih, Rr. Arum; Dzaljad, Rifma Ghulam (Faculty of Health Sciences, Syarif Hidayatullah State Islamic University of Jakarta, 2023)
AbstractFather's support is one of the influential factors in the success of exclusive breastfeeding. The concept of the Health Belief Model has not been applied to gain an understanding of exclusive breastfeeding behavior from the perspective of fathers. This study aims to describe the role and perceptions of fathers in supporting exclusive breastfeeding using the Health Belief Model concept. The study took place in South Tangerang City and was conducted using a qualitative method involving 5 couples who have children aged 6-24 months and have successfully achieved exclusive breastfeeding. Data collection was done through focus group discussions, and data validation was achieved through source triangulation. All fathers played a role by providing both physical and emotional support. They had perceptions of the benefits of exclusive breastfeeding for their babies and wives. Perceived barriers stemmed from work, wives, and parents/in-laws. Some informants had low perceptions of threat in supporting breastfeeding. Positive perceptions of exclusive breastfeeding encourage fathers to play a supportive role. Education regarding the benefits of exclusive breastfeeding should be provided to fathers and grandparents. Advocacy for paternity leave or work-from-home is needed to support exclusive breastfeeding.Keywords: Exclusive Breastfeeding, Father Role, Health Belief Model